2012
DOI: 10.1002/jbm.a.34383
|View full text |Cite
|
Sign up to set email alerts
|

High protein adsorptive capacity of amino acid‐functionalized hydroxyapatite

Abstract: Charged functional groups present on the surface of biomaterials play an important role to regulate the affinity and attachment of macromolecules, including proteins, on the surface of biomaterials. In this study, the protein adsorptive capacity of hydroxyapatite (HA) was regulated by introducing different amino acids during the precipitation of HA. After incubation of HA samples in 5000 μg/mL lysozyme solution at pH 7.4 for 24 h, unmodified HA adsorbed 0.886 mg/m(2) of lysozyme while amino acid-functionalized… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
31
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(31 citation statements)
references
References 41 publications
0
31
0
Order By: Relevance
“…The results demonstrated that MHA had a greatly improving protein loading capacity, nearly double that of HA. A number of factors are important in determining the amount of protein adsorbed on surfaces [6,10,16,17,20]. A higher surface area generally corresponds to a higher amount of protein adsorption [10,16].…”
Section: Quantity Of Protein Adsorption Depended On Timementioning
confidence: 99%
See 2 more Smart Citations
“…The results demonstrated that MHA had a greatly improving protein loading capacity, nearly double that of HA. A number of factors are important in determining the amount of protein adsorbed on surfaces [6,10,16,17,20]. A higher surface area generally corresponds to a higher amount of protein adsorption [10,16].…”
Section: Quantity Of Protein Adsorption Depended On Timementioning
confidence: 99%
“…The adsorption behaviors of large biomolecules onto hydroxyapatite have been frequently studied [16,17,19,22]. To our knowledge, attention has been focused on the amount of adsorption for large biomolecules, while models of adsorption onto MHA have scarcely been mentioned in the previous papers.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…where β hkl is the full width at half maximum in radians, Ɵ is the diffraction angle for plane (hkl), K is the constant depending on crystal habit (chosen as 0.94) and λ is the wavelength of Cu Kα radiation (1.5406Å) [12].…”
Section: X-ray Diffraction (Xrd)mentioning
confidence: 99%
“…Additionally, HA crystals carry two different protein binding sites on its surface, e.g. P and C sites that can bind to positively cationic groups such as NH 3 + or negatively charged anionic groups such as COO -, respectively [12].…”
mentioning
confidence: 99%